Implementing Mail Administration Using the Codeigniter Framework - Devit Suwardiyanto; Junaedi Adi Prasetyo; Umihanik Nor Aliza; Mohamad Dimyati Ayatullah (Jurnal Jaringan Telekomunikasi, 2022)
Administration is the activity of systematically managing and recording data information to provide various information and also make it easier to retrieve it either partially or completely. The administration of mailing at SMK Negeri 1 Glagah is still conventional by recording incoming and outgoing mail using a book and storing the mail in an uncertain places. Some of the problems that can be solved with information technology, one of which is the storage of incoming and outgoing mail at SMK Negeri 1 Glagah. With a mail administration application that uses the CodeIgniter Framework and MySQL database, teachers who being admins or operators can directly enter incoming and outgoing mail data in the application, and they can directly distribute the mail to the receiver person through the application. Teacher who receive the mail will get a notification on the application if there is a new mail coming in. With the Mail Administration Application, staff and school principals can find out the existing mail data easily and computerized with accurate and archived data. The results of the questionnaire recapitulation can be concluded that the overall application quality level is in Good criteria, with a percentage of 84.33%.